Improving Financial Administration and Customer Database at Rinawatiwati Homedecor MSME - Audita Nuvriasari; Natalia Ersa Angela; Yohana Manek; Muhammad Akram Habiullah; Annisa Salsabila Khasanah; Aji Bayu Sanjoyo; Shinta Nur Khoirothi (International Journal of Community Service Implementation, 2025)
The important role of MSMEs as the backbone of the Indonesian economy requires support through improved business governance, enabling them to achieve optimal business performance. The purpose of this community service activity is to improve partners' knowledge and skills in financial administration, including recording daily financial transactions in cash books and preparing profit and loss reports and balance sheets. Another objective is to improve knowledge and skills in marketing administration, particularly customer database management. The activity implemented using a counseling method consisting of education and training with hands-on practice. The results of the activity indicate that partners understand how to record business finances using both manual and digital methods. Furthermore, partners can create customer data, one of which is intended for promotional purposes. To maintain consistency in financial and marketing administration, continuous monitoring and mentoring are still necessary so that the program can run effectively and have an impact on improving business performance